A Review and Hypothesized Model of the Mechanisms That Underpin the Relationship Between Inflammation and Cognition in the Elderly - Tangestani Fard, Masoumeh; Stough, Con (Frontiers in Aging Neuroscience, 2019)
Age is associated with increased risk for several disorders including dementias, cardiovascular disease, atherosclerosis, obesity, and diabetes. Age is also associated with cognitive decline particularly in cognitive domains associated with memory and processing speed. With increasing life expectancies in many countries, the number of people experiencing age-associated cognitive impairment is increasing and therefore from both economic and social terms the amelioration or slowing of cognitive ageing is an important target for future research. However, the biological causes of age associated cognitive decline are not yet well understood. In the current review, we outline the role of inflammation in cognitive ageing and describe the role of several inflammatory processes, which have a direct effect on brain function and indirect effects on brain function via changes in cardiovascular function.